1992
DOI: 10.1002/nme.1620330702
|View full text |Cite
|
Sign up to set email alerts
|

The superconvergent patch recovery and a posteriori error estimates. Part 1: The recovery technique

Abstract: SUMMARYThis is the first of two papers concerning superconvergent recovery techniques and a posteriori error estimation. In this paper, a general recovery technique is developed for determining the derivatives (stresses) of the finite element solutions at nodes. The implementation of the recovery technique is simple and cost effective. The technique has been tested for a group of widely used linear, quadratic and cubic elements for both one and two dimensional problems. Numerical experiments demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,076
0
8

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,847 publications
(1,113 citation statements)
references
References 20 publications
6
1,076
0
8
Order By: Relevance
“…By comparing the zeros of u k and s k (see Table 4 and Table 5) one can conclude that an O(h k+2 ) convergence is impossible to happen mathematically with a straightforward application of the Taylor's Series paradigm. Therefore, the ultraconvergence phenomenon as notified by Zienkiewicz in his numerical experiments are believed to be a numerical coincidence (see reference [13]). It is important to comment the existence of purely imaginary ultraconvergent zeros as one can infer from Table 4.…”
Section: Definition Of Hyperconvergent Pointsmentioning
confidence: 89%
See 1 more Smart Citation
“…By comparing the zeros of u k and s k (see Table 4 and Table 5) one can conclude that an O(h k+2 ) convergence is impossible to happen mathematically with a straightforward application of the Taylor's Series paradigm. Therefore, the ultraconvergence phenomenon as notified by Zienkiewicz in his numerical experiments are believed to be a numerical coincidence (see reference [13]). It is important to comment the existence of purely imaginary ultraconvergent zeros as one can infer from Table 4.…”
Section: Definition Of Hyperconvergent Pointsmentioning
confidence: 89%
“…The superconvergence is also linked to the concept of reduced integration and zero energy modes so important in the Finite Element Theory [15]. Even more important, the superconvergence points are of utility as sampling points for the finite element designers in formulations like gradient smoothening or gradient recovery in the sense of The Superconvergent Patch Recovery as sketched by Zienkiewcz [13]. However, the major significance of these points that explains all kind of numerical and analytical studies in this topic refers to its application in adaptive finite element analysis, especially for construction of error indicators based on the recovered gradient or hessian.…”
Section: Definition Of Superconvergencementioning
confidence: 99%
“…Regarding accuracy, our numerical experiments showed that this strategy produced sufficiently reliable results. We note that improvements of the accuracy can be obtained using gradient recovery techniques which yield superconverging behaviour (Zienkiewicz and Zhu 1992). The aim of this study is to investigate the impact of oscillatory and pulsating boundary conditions on the volume flow rate at the right end of the tube.…”
Section: Finite Element Discretisationmentioning
confidence: 99%
“…Using a stress recovery technique such as the Super-convergent Patch Recovery (SPR) theory ( [29], [30]), the raw stress field may be recovered resulting in significantly improved results. Next to the fact that only the singular modes have to be smoothed on the boundary, numerical experiments have shown that excellent results can still be achieved by only recovering the stresses over a few element in the general crack extension direction, further reducing computational cost.…”
Section: Calculation Of Stress Intensity Factorsmentioning
confidence: 99%